Big plant closures and agglomeration economies - Jofre-Monseny, Jordi; Sánchez-Vidal, Maria; Viladecans-Marsal, Elisabet (Barcelona, 2015)
"This paper analyses the effects of large manufacturing plant closures on local employment. Specifically, we estimate the net employment effects of the closure of 45 large manufacturing plants in Spain, which relocated abroad between 2001 and 2006. We run differences-in-differences specifications in which locations that experience a closure are matched to locations with similar pre-treatment employment levels and trends. The results show that when a plant closes, for each job directly lost in the plant closure, between 0.3 and 0.6 jobs are actually lost in the local economy. The adjustment is concentrated in incumbent firms in the industry that suffered the closure, providing indirect evidence of labor market pooling effects. We find no employment effects in the rest of manufacturing industries or in the services sectors. These findings suggest that traditional input-output analyses tend to overstate the net employment losses of large plant closures."